Proceedings of the 2003 International Conference on Machine Learning and Cybernetics (IEEE Cat. No.03EX693)
DOI: 10.1109/wsc.2003.1261649
|View full text |Cite
|
Sign up to set email alerts
|

The use of simulation to evaluate hospital operations between the emergency department and a medical telemetry unit

Abstract: This paper presents a simulation model of the operations in the Emergency Department (ED) and Medical Telemetry (Med Tele) Units at Rush North Shore Medical Center. The model allows management to see the operations of both units as well 3s how the processes of each unit impact the other. Due to the large amount of variability that can take place within these units, Rush North Shore Medical Center along with Cap Gemini Emst & Young sought the use of simulation to help evaluate thei operations and provide insigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
3

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 0 publications
0
31
0
3
Order By: Relevance
“…Approaches taken include assessment of working practices [1,[3][4][5], shift patterns [5], equipment bottlenecks [9], and in some cases, patient pathways themselves [20]. Interactions of ED patient flow with the wider hospital context are clearly also important [7], and examination of these interactions can be achieved using DES models, or sometimes may be better analysed by other techniques [29,32].…”
Section: Pathway Redesign In Emergency Departmentsmentioning
confidence: 99%
“…Approaches taken include assessment of working practices [1,[3][4][5], shift patterns [5], equipment bottlenecks [9], and in some cases, patient pathways themselves [20]. Interactions of ED patient flow with the wider hospital context are clearly also important [7], and examination of these interactions can be achieved using DES models, or sometimes may be better analysed by other techniques [29,32].…”
Section: Pathway Redesign In Emergency Departmentsmentioning
confidence: 99%
“…The simulation looked at the possibility of reducing a patient's length of stay and sought out ways to improve operations and communication between the two units. The study found that process improvement was able to increase if fewer patients were admitted or additional beds were added in the Medical Telemetry Unit (Blasak, 2003).…”
Section: Research Simulationsmentioning
confidence: 99%
“…However, DES in particular has seen an increase in application covering almost all areas of healthcare in the past decade [13]. DES has been used in Emergency Departments (ED) for modelling operations and for the analysis of patient flows and throughput time [11], [3], [5], [7], and [6]. Others have used DES to forecast future capacity requirements and expansion of new or existing ED facilities [8], [9].…”
Section: Introductionmentioning
confidence: 99%